Didactic Design on the Circumference and Area of Plane in Grade 4 Elementary Education - Irfan Fauzi; Indra Suhendra; Lina Marlina Nur Rizkiya; Sartono Sartono; Asep Safa'at (International Conference on Elementary Education, 2020)
Geometry becomes very important material for students in elementary school, because it can encourage students to be able to think critically and solve problems in everyday life. One of the geometry materials taught in 4th grade elementary school is understanding about the circumference and area of plane. This study aims to develop a didactic design on the circumference and area of plane in grade 4 elementary school. This research used the research design method with the development method of didactical design research (DDR), the researcher conducted an obstacle learning test for students to see the obstacles experienced by students in understanding the circumference and area of plane, learning obstacle is used as material in making a learning trajectory which can then be used in developing didactic designs, so this research resulted in a hypothetical didactic design of the circumference and area of plane in grade 4 elementary school